Lingkungan dan Pembangunan Perdamaian: Refleksi Kasus Aceh - Ucu Martanto (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2009)
The role of environment is like a two sided coin. Once it can be seen as underlying cause of conflict, but at the other side it is useful to build sustainable peace. Nevertheless, the discourse on peace building through environmental cooperation in Indoneisa is less discussed than environmentally induces conflict. This condition creates an imbalance understanding of the inherent roles of environment, either to build peace or to create conflict. The article aims to reflect both environmental roles in the case of Aceh. From the environmental perspective, peace building processes in Aceh that have been started since MoU Helsinki should be incorporating two rutes in the same manner. First, government of Aceh and other stakeholders need to muffle all factors (foremost environmental factors) that potentially shape a new conflict. Second, environmental cooperation initiatives are needed to strengthen social cohesion and eliminate environmental injustice.